‘Bridging the gap’: school resource officers as bridge builders in the community policing era - Higgins, Ethan M. (Journal of crime and justice, 2020)
Since their origination in the 1950s, school resource officers (SROs) have become increasingly commonplace in schools throughout the United States. In turn, researchers have developed a considerable base of empirical work on SRO roles and how these roles motivate action in public schools. A large part of this empirical work has focused on roles that fall outside conventional law enforcement duties such as when officers act as mentors, counselors, and educators. However, this line of research has not yet investigated the motivations for why SROs engage in non-law enforcement roles. The purpose of the current study is to draw from 26 interviews with SROs to explore the motivations for engaging in non-law enforcement roles and activities in public schools. Findings illustrate that SROs identify the overarching motivation of non-law enforcement as ‘bridging the gap,’ where they seek out at-risk students and connect them to necessary resources in the school and community. We find that SROs engage in building four types of bridges. The findings also suggest that SROs draw from a community-oriented policing framework to explain this motivation.